1979
DOI: 10.1002/kin.550110711
|View full text |Cite
|
Sign up to set email alerts
|

Absolute rate constants for the reaction of bromine atoms with ozone from 234 to 360 K

Abstract: The rate constant for the reaction of Br + 0 3 -BrO + 0 2 has been measured a t four temperatures from 234 to 360 K by the technique of discharge flow coupled with resonance-fluorescence detection of bromine atoms. The measured rate constants obey the Arrhenius expression k = (9.45 f 2.48) X exp(-659 f 64/T) cm3/molec-sec (one standard deviation). The results are compared with two previous studies, one of which utilized the flashphotolysis-resonance-fluorescence technique and the other utilized the discharge-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
(14 reference statements)
2
2
0
Order By: Relevance
“…16 This similarity supports the suggestion from the early kinetic studies that the transition-state structures of these reactions were mostly determined by the configuration of the ozone molecule. [10][11][12] The similarity also qualitatively agrees with the theoretical calculations, which indicated that the configuration of the reaction intermediate was like that of the ozone molecule 9,15 and is consistent with the argument by Schaefer and co-workers that ozone electronic structure plays an important role in the reaction mechanism. 28 O 3 molecule can be characterized as a diradical with the two unpaired π electrons in the terminal O atoms.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…16 This similarity supports the suggestion from the early kinetic studies that the transition-state structures of these reactions were mostly determined by the configuration of the ozone molecule. [10][11][12] The similarity also qualitatively agrees with the theoretical calculations, which indicated that the configuration of the reaction intermediate was like that of the ozone molecule 9,15 and is consistent with the argument by Schaefer and co-workers that ozone electronic structure plays an important role in the reaction mechanism. 28 O 3 molecule can be characterized as a diradical with the two unpaired π electrons in the terminal O atoms.…”
Section: Discussionsupporting
confidence: 87%
“…A large number of kinetic studies on ozone reactions with radicals such as Cl + O 3 and Br + O 3 have been carried out. Preexponential factors of these reactions were found to be very similar and insensitive to the reaction exothermicity; ,, the rate coefficients for these reactions correlated with electron affinities of the radical atoms instead of the reaction exothermicity . It was suggested that the transition-state structures of these reactions were insensitive to the radical, and these reactions proceeded via early transition states that best resembled the reactant ozone. ,, On the basis of the information from the kinetic studies, the reaction Br + O 3 is expected to be very similar to the reaction Cl + O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Bromine atom resonance radiation was produced by a microwave discharge lamp fitted with a sapphire window and charged with 0.5 torr flowing premixed mixture of Br2 in helium (XBr • 0.0002). Previous experience Michael and Payne, 1979] had shown that this low molecular fraction of bromine in the resonance lamp prevents any substantial line reversal in the resonance source, thus avoiding nonlinearity in first-order decay plots due to the resonance source. The spectrum of an identically operated lamp had previously been recorded with a McPherson 218 vacuum monochromator , and the multiplet intensities were similar to those reported for a pure Doppler source [Clyne and Townsend, 1974] The extremely low rate constant for Br + C2He would thus be explicable if there was a fairly strong temperature dependence as observed for NH 2 or H. But we observe no measurable temperature dependence for Br + C2H2 from 210 to 393 K. An A factor for this reaction of the order of 10-•5 cm 3 s-• is therefore implied.…”
Section: Methodssupporting
confidence: 65%
“…Several previous studies from this laboratory have involved the determination of rate constants for reactions involved in the catalytic chain destruction of the earth's ozone layer by C1 atoms [Whytock et al, 1977; or Br atoms Michael and Payne, 1979;Nava et al, 1981]. While the rate constants for the reactions of C1 and Br atoms with many major stratospheric species are now well established [DeMore, 1983], there is a need to determine the rate const•ints for the reactions of these atoms with minor hydrocarbon species [Rudolph et al, 1981[Rudolph et al, , 1984Cronn and Robinson, 1979; Whitby and Altwicker, 1978] such as acetylene, which has a mixing ratio of 10-•o to 10-• • in the troposphere and lower stratosphere.…”
Section: Introductionmentioning
confidence: 99%